'Greenwich near London': the Royal Observatory and its London networks in the seventeenth and eighteenth centuries. Issue 2 (14th May 2019) - HIGGITT, REBEKAH
Abstract: Built in Greenwich in 1675–1676, the Royal Observatory was situated outside the capital but was deeply enmeshed within its knowledge networks and communities of practice. Scholars have tended to focus on the links cultivated by the Astronomers Royal within scholarly communities in England and Europe but the observatory was also deeply reliant on and engaged with London's institutions and practical mathematical community. It was a royal foundation, situated within one government board, taking a leading role on another, and overseen by Visitors selected by the Royal Society of London. These links helped develop institutional continuity, while instrument-makers, assistants and other collaborators, who were often active in the city as mathematical authors and teachers, formed an extended community with interest in the observatory's continued existence. After outlining the often highly contingent institutional and personal connections that shaped and supported the observatory, this article considers the role of two early assistants, James Hodgson and Thomas Weston. By championing John Flamsteed's legacy and sharing observatory knowledge and practice beyond its walls, they ensured awareness of and potential users for its outputs. They and their successors helped to develop a particular, and ultimately influential, approach to astronomical and mathematical practice and teaching.